Evaluation of the effects of active fractions of chinese medicine formulas on IL-1β, IL-6, and TNF-α release from ANA-1 murine macrophages. (17th February 2016) - Ni, Li-Jun; Wang, Nan-Nan; Zhang, Li-Guo; Guo, Yan-Zi; Shi, Wan-Zhong
Abstract: Ethnopharmacological relevance: Yaotongning (YTN) is a traditional Chinese Medicine (TCM) that contains ten component medicinal materials (CMMs) and uses Chinese rice wine as a vehicle to enhance its efficacy. YTN has been used for rheumatoid arthritis (RA) treatment in China for decades and has been reported to have anti-inflammatory and analgesic effects, as well as to strengthen the immune system. Aim of the study: The present work quantitatively evaluated the in vitro effects of active fractions from the ten CMMs that make up YTN and eight additional herbs commonly used in TCM formulas for RA treatment, as well as different combinations of these active fractions, on cellular immune response; the findings were used to determine which active fractions are responsible for promoting an immune response, and to assess whether YTN is superior to other similar formulas and whether YTN can be improved by simplifying its formula from the point of its cellular immunomodulatory activity. Materials and methods: Using the YTN formulation principles and some concepts in combinatorial chemistry, 27 TCM samples were designed by combining some or all of the active fractions of YTN and other eight herbs used for RA treatment. Release of interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) from ANA-1 murine macrophages was measured using an enzyme-linked immunosorbent assay (ELISA). The immunoregulatory effects of the TCM samples were evaluated by comparing their half-effective concentrations (EC50 ) for stimulating the release of these cytokines. Results: Among the investigated active fractions, the flavonoids from Carthamus tinctorius (Fct), Davallia mariesii (Fdm), and Cinnamomum cassia Twig volatile oils (Vca) from the eight selected herbs effectively promoted IL-1β and IL-6 release from ANA-1 cells. Saponins from the YTN CMM Glycyrrhiza uralensis (Sgu) were the most potent promoters of IL-1β and TNF-α release. The aqueous extract of YTN CMM Eupolyphaga sinensis (Ves) strongly enhanced the release of IL-1β, IL-6, and TNF-α from ANA-1 cells. The EC50 values for stimulating the secretion of IL-1β, IL-6, and TNF-α could be determined for only six samples. The full YTN formula and the sample containing 50% Glycyrrhiza uralensis saponins, 25% of the mixture of alkaloids, and 25% of the mixture of all flavonoids exhibited good comprehensive cellular immunomodulatory activity. The immunomodulatory activity of the complete YTN formula was better than that of the sample containing all active fractions of YTN without Chinese rice wine (the YTN vehicle). Conclusions: Sgu and Ves are the primary active fractions of YTN involved in stimulating immune responses. The YTN prescription was reasonably effective at promoting cellular immune responses. Chinese rice wine, the YTN vehicle, strengthened the immunoregulatory activity of YTN. The results of this study demonstrate that the YTN recipe could be improved by reducing the number of CMMs and altering some active fractions without reducing its activity to promote cellular immune responses. Graphical abstract: